2011
DOI: 10.1111/j.1600-9657.2010.00967.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of multiple traumatized anterior teeth associated with an alveolar bone fracture in a 15-year-old schoolboy: a 2.5-year follow up

Abstract: We report a case of multiple dental traumas in a 15-year-old school boy who was hit by a stone. Clinical examinations revealed the avulsion of teeth 21, 22, and 23, an uncomplicated crown fracture of tooth 41, and a complicated crown fracture (CCF) of teeth 11, 31, and 33. An alveolar bone fracture and a root fracture in the apical third of tooth 23 were as well noted on radiographs. The avulsed teeth were replanted and rigidly splinted after an extraoral dry time of 90 min. Endodontic treatments were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Glass fiber‐reinforced composite resin has been clinically tested also as space maintainer . Additionally, the stabilization and conservative treatment of multiple traumatized anterior teeth have been reported . Moreover, a non‐invasive technique with space maintainer using fiber‐reinforced composite and natural tooth has been proposed .…”
Section: Discussionmentioning
confidence: 99%
“…Glass fiber‐reinforced composite resin has been clinically tested also as space maintainer . Additionally, the stabilization and conservative treatment of multiple traumatized anterior teeth have been reported . Moreover, a non‐invasive technique with space maintainer using fiber‐reinforced composite and natural tooth has been proposed .…”
Section: Discussionmentioning
confidence: 99%
“…A few case reports described the diagnosis of alveolar fracture by using radiographs 3,10 while some other case reports affirmed that CBCT is an effective diagnostic method for minor alveolar fractures 11,15,18 . Our study showed lower AUR numbers in the detection of alveolar fractures, when compared with root fractures, by CBCT.…”
Section: Discussionmentioning
confidence: 99%
“…One case reported in 2011 (20) refers to the consequences of a stone impact on the face of a 15‐year‐old male patient, which caused a multiple‐tooth trauma in which three teeth were avulsed and others were fractured. The impact resulted in an intrusive luxation leading to pulp necrosis.…”
Section: Discussionmentioning
confidence: 99%